Fixed Point Theorem For Fuzzy Mapping - Rajesh Shrivastava; Megha Shrivastava (International Journal of Mathematics And its Applications, 2016)
In this paper we state and prove fixed fuzzy point theorem for fuzzy mapping in complete metric space.